1987
DOI: 10.1192/bjp.150.5.685
|View full text |Cite
|
Sign up to set email alerts
|

Lithium in the Treatment of Aggression in Mentally Handicapped Patients

Abstract: In a double-blind trial lasting 4 months in 42 mentally handicapped patients, the effect of lithium on aggression was assessed in comparison with placebo. In the lithium-treated group, 73% of patients showed a reduction in aggression during treatment. There were significant differences in mean weekly aggression scores and in the frequency of aggressive episodes between the lithium and placebo groups. Side-effects were noted in 36% of the lithium group (and 20% of the placebo group), but were mainly transitory.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

1987
1987
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(32 citation statements)
references
References 16 publications
0
30
0
1
Order By: Relevance
“…Mood stabilizers lithium Oral 2 [28,29] Two randomized inpatient trials, one industry sponsored [29] (Regan, personal communication), the other not [28] Both trials had a placebo run-in before randomization but showed benefit with lithium treatment Benzodiazepines Oral/ injectable 1 [17] Clinical opinion only Widely used, without good evidence Anger management Group 2 [30,31] Two randomized trials Both trials are encouraging and have led to a large, funded, randomized trial with Prof. P. Willner as principal investigator (HTA 08/53/34, UKCRN ID 7089 [32] )…”
Section: Antipsychotic Drugsmentioning
confidence: 96%
“…Mood stabilizers lithium Oral 2 [28,29] Two randomized inpatient trials, one industry sponsored [29] (Regan, personal communication), the other not [28] Both trials had a placebo run-in before randomization but showed benefit with lithium treatment Benzodiazepines Oral/ injectable 1 [17] Clinical opinion only Widely used, without good evidence Anger management Group 2 [30,31] Two randomized trials Both trials are encouraging and have led to a large, funded, randomized trial with Prof. P. Willner as principal investigator (HTA 08/53/34, UKCRN ID 7089 [32] )…”
Section: Antipsychotic Drugsmentioning
confidence: 96%
“…Lithium is used in the management of mania, bipolar disease, and aggression associated with personality disorders [139] and intellectual disabilities [140]. Its primary action is to alter sodium transport and increase intracellular metabolism of catecholamines.…”
Section: Lithiummentioning
confidence: 99%
“…Lithium was added to existing medication regimens in order to target aggression. Seventy-three percent improved and 9% got worse when treated with lithium carbonate compared to 30% improved with placebo [85]. A second study had a double blind, controlled crossover design with N = 52.…”
Section: Lithium Carbonatementioning
confidence: 97%